Analisis Perbandingan Daya Tahan Komposit Serat Alam dan Serat Sintetis pada Lingkungan Produksi Bersuhu Tinggi - Sabikah, Sabikah Nur Nayla; M.Irfan Syahputra; Lindi Cistia Praba (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to analyze the comparison of the durability of natural fiber and synthetic fiber composites in a high-temperature production environment. Testing was conducted on carbon fiber, aramid (synthetic), ramie, and jute (natural) fiber-based composites with exposure to temperatures of 80-150°C for 500 hours. The parameters measured include tensile strength, elastic modulus, dimensional stability, morphological changes, and moisture absorption. The research results show that synthetic fiber composites have superior durability compared to natural fibers. Carbon fiber composites retain 87% of their initial tensile strength with only a 4.2% reduction in modulus, while flax fibers only retain 62% strength with a 26% reduction in modulus. Microscopic analysis revealed significant delamination in natural fiber composites with interface gaps of 15-25 μm, compared to 3-5 μm in synthetic fibers. Natural fibers undergo thermal degradation due to the decomposition of lignin and hemicellulose, resulting in significant color changes and a dimensional shrinkage of 3.2%. The moisture absorption of natural fibers increases to 8.5% after exposure, indicating damage to the cellular structure. This research concludes that synthetic fiber composites are more suitable for long-term high-temperature production applications, but natural fibers can still be considered for low-temperature applications with appropriate chemical modification.